The Policy Changes of State-Owned Enterprises Concerning Foreigner in the Perspective of Talcott Persons Structural Functional Theory - Andre Arya Pratama; Anggun Nurfani; Rilda Murniati (Fakultas Hukum Universitas Lampung, 2025)
Law Number 16 of 2025 allows foreign nationals to occupy strategic positions in State-Owned Enterprises, triggering debate between the demands of modernization in a globalized economy and the principle of national economic sovereignty under Article 33 of the 1945 Constitution. This normative legal study applies a statute approach, an analytical approach, and Talcott Parsons’ AGIL framework to examine the legal and sociological implications of this policy. The findings show that the policy functions as an adaptive strategy to improve governance and competitiveness, but it also raises challenges in integrating international professional standards with local organizational culture and in maintaining economic nationalism. While foreign involvement may reduce political pressures in decision making, it simultaneously generates resistance related to the sovereignty of public resources. The effectiveness of this policy therefore depends on the ability of the legal system and SOE management to balance global openness with the preservation of national values, supported by clear implementing regulations and mechanisms for domestic capacity building through knowledge transfer.